Production of p-cresol by Decarboxylation of p-HPA by All Five Lineages of Clostridioides difficile Provides a Growth Advantage - Harrison, Mark A.; Kaur, Harparkash; Wren, Brendan W.; Dawson, Lisa F. (Frontiers in Cellular and Infection Microbiology, 2021)
Clostridioides difficile is the leading cause of antibiotic associated diarrhoea and is capable of causing severe symptoms such as pseudomembranous colitis and toxic megacolon. An unusual feature of C. difficile is the distinctive production of high levels of the antimicrobial compound para-cresol. P-cresol production provides C. difficile with a competitive colonisation advantage over gut commensal species, in particular Gram-negative species. p-cresol is produced by the conversion of para-hydroxyphenylacetic acid (p-HPA) via the actions of HpdBCA decarboxylase coded by the hpdBCA operon. Host cells and certain bacterial species produce p-HPA, however, the effects of p-HPA on viability of C. difficile and other gut microbiota is unknown. Here we show that representative strains from all five C. difficile clades are able to produce p-cresol by two distinct mechanisms; i) via fermentation of p-tyrosine and ii) via uptake and turnover of exogenous p-HPA. We observed strain specific differences in p-cresol production, resulting from differential efficiency of p-tyrosine fermentation; representatives of clade 3 (CD305) and clade 5 (M120) produced the highest levels of p-cresol via tyrosine metabolism, whereas the toxin A/B+ isolate from clade 4 (M68) produced the lowest level of p-cresol. All five linages share at least 97.3% homology across the hpdBCA operon, responsible for decarboxylation of p-HPA to p-cresol, suggesting the limiting step in p-cresol production may result from tyrosine to p-HPA conversion. We identified that elevated intracellular p-HPA, modulated indirectly via CodY, controls p-cresol production via inducing expression of the HpdBCA decarboxylase ubiquitously in C. difficile populations. Efficient turnover of p-HPA is advantageous to C. difficile as p-HPA has a deleterious effect on growth of C. difficile and other representative Gram-negative gut bacteria, transduced potentially by disruption of membrane permeability, and release of intracellular phosphate. This study provides insights into the importance of the HpdBCA decarboxylase in C. difficile pathogenesis, both in terms of p-cresol production and detoxification of p-HPA, highlighting its importance to cell survival and as a highly specific therapeutic target for inhibition of p-cresol production across the C. difficile species.